Recruiting Adolescent Research Participants: In-Person Compared to Social Media Approaches - Moreno, Megan A; Waite, Alan; Pumper, Megan; Colburn, Trina; Holm, Matt; Mendoza, Jason (Cyberpsychology, behavior and social networking, 2017)
Recruiting adolescent participants for research is challenging. The purpose of this study was to compare traditional in-person recruitment methods to social media recruitment. We recruited adolescents aged 14-18 years for a pilot physical activity intervention study, including a wearable physical activity tracking device and a Facebook group. Participants were recruited (a) in person from a local high school and an adolescent medicine clinic and (b) through social media, including Facebook targeted ads, sponsored tweets on Twitter, and a blog post. Data collected included total exposure (i.e., reach), engagement (i.e., interaction), and effectiveness. Effectiveness included screening and enrollment for each recruitment method, as well as time and resources spent on each recruitment method. In-person recruitment reached a total of 297 potential participants of which 37 enrolled in the study. Social media recruitment reached a total of 34,272 potential participants of which 8 enrolled in the study. Social media recruitment methods utilized an average of 1.6 hours of staff time and cost an average of $40.99 per participant enrolled, while in-person recruitment methods utilized an average of 0.75 hours of staff time and cost an average of $19.09 per participant enrolled. Social media recruitment reached more potential participants, but the cost per participant enrolled was higher compared to traditional methods. Studies need to consider benefits and downsides of traditional and social media recruitment methods based on study goals and population.